The The Effect Range of Motion (ROM) Therapy and Transcutaneous Electrical Nerve Stimulation on Improving Extremity Muscle Strength in Stroke Patients - Masitaningsih, Dewi; Suyanto, Suyanto (Journal of Smart Nursing and Health Science, 2026)
Background: Stroke is one of the leading causes of disability that often results in impaired motor function, particularly decreased muscle strength in the extremities. Physical rehabilitation is essential to improve the functional ability of stroke patients, one of which is through a combination of Range of Motion (ROM) therapy and Transcutaneous Electrical Nerve Stimulation (TENS). This study aims to determine the effect of ROM and TENS therapy on increasing extremity muscle strength in stroke patients at Sari Asih Ciledug Hospital. Methods: This study used a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 88 stroke patients selected using purposive sampling technique. The intervention included ROM and TENS therapy according to hospital standards. Muscle strength was measured before and after the intervention using Manual Muscle Testing (MMT). Data were analyzed using the Wilcoxon Signed Rank Test. Results: The results showed that before the intervention, most respondents had moderate (51.1%) and poor (39.8%) muscle strength. After receiving ROM and TENS therapy, there was an increase in muscle strength with moderate category at 65.9% and good category at 22.7%. The Wilcoxon test result showed p = 0.000 (p < 0.05), indicating a significant effect of ROM and TENS therapy on increasing extremity muscle strength in stroke patients. Conclusion: ROM and TENS therapy have a significant effect on improving extremity muscle strength in stroke patients. This therapy can be recommended as a non-pharmacological intervention in stroke rehabilitation programs to enhance motor function and patient independence